Safety of existing bridges with a long period of good service based on the theory of reliability - Melo, Marcelo [UNESP]; Stucchi, Fernando [UNESP]; Candido, Camila [UNESP] (My University, 2024)
Brazil’s infrastructure is getting old, and many of its bridges have been in service for over five decades without any structural issues. The absence of project records in most cases necessitates engineers to evaluate these structures. Traditional safety analyses, considering as usual a little higher load, and applying standard criteria used for new constructions, have proven inadequate. This inadequacy arises from the likelihood that permissible deviations in design of new structures could be greater when comparing already-built structures, due to potential meticulous construction precision, that justifies their prolonged service life. To address this issue, the current Brazilian bridge code incorporates provisions, for reducing partial safety factors for existing structures with many years of good service, based on the Eurocode. This article uses reliability theory to investigate the extent to which superior construction quality—manifested through minimized construction deviations and material property variability—contributes to the observed long-term performance of these bridges. Additionally, the article explores the feasibility of revising the reference period for accidental loads from the standard 50 years for new constructions to a shorter duration, such as 30 years. This adjustment aims to extend the service life of these structures. A case study will be presented, focusing on a bridge in São Paulo. This bridge, constructed in 1950, initially accommodated a lighter live load action than prescribed by contemporary standards. Subsequently, it required widening to accommodate increasing traffic and meet current code requirements for load-bearing capacity.